The Impact of Sodium Chloride (NaCl) Concentrations on Electrocoagulation for Simultaneous Tartrazine Dye Removal and Hydrogen Production - Saddam Husein; Slamet; Eniya Listiani Dewi (Engineering Proceedings, 2024)
Liquid waste frequently contains a large variety of hazardous substances, including tartrazine-based dyes. These color compounds can present a significant hazard to both human health and the natural environment. Moreover, there is a growing demand for sustainable energy, and hydrogen is emerging as a promising alternative energy source that does not produce carbon emissions. To address the aforementioned concerns, it is necessary to conduct research aimed at eradicating tartrazine while concurrently generating hydrogen gas as a viable substitute for energy. This study aims to investigate the effect of different concentrations of NaCl electrolytes on the rate of simultaneous tartrazine elimination and hydrogen production using electrocoagulation. The electrocoagulation procedure was used with various concentrations of NaCl (0, 0.2, 0.4, 0.6, 0.8, and 1 g/L). UV–Vis spectrophotometers and gas chromatography were employed to evaluate the elimination of tartrazine and the rate of hydrogen production. The results show that the highest rate of tartrazine removal was 93%, which occurred at 0.8 and 1 g/L of NaCl at 240 min. It can be stated that higher electrolyte concentrations generally lead to an increase in tartrazine removal. The highest rate of hydrogen production was 217.44 mol H2/m2, which occurred at 1 g/L of NaCl at 240 min; thus, it can be concluded that higher electrolyte concentrations generally lead to an increase in hydrogen production.